Risk factors for oral cancer: Thematic trends and research agenda - Orlando Pérez-Delgado; Pablo Alejandro Millones-Gómez; Alejandro Valencia-Arias; David Yeret Rodríguez-Salazar (GarVal Editorial Ltda., 2023)
Context: Oral cancer is difficult to define due to several factors. It's known as oral squamous cell carcinoma (OSCC) and is common in the head and neck. Geographic variations in the impact of OSCC highlight the need for research on risk factors and treatment trends. Aims: To identify the main research trends of studies on oral cancer risk factors in the scientific literature in the Scopus database and Web of Science. Methods: This was an exploratory study of the risk factors for oral cancer designed considering the eligibility criteria defined by the PRISMA-2020 international statement, that is, inclusion and exclusion. Results: A total of 215 documents from Scopus and Web of Science were subjected to bibliometric analysis. The years 2020 and 2021 were the most productive, with 18 and 22 articles, respectively. The leading author in productivity and impact was Johnson N, the leading journal was Oral Oncology, followed by the International Journal of Cancer, and the main contributing countries were the United States, the United Kingdom and India. The main thematic cluster was composed of concepts such as Tobacco and Alcohol as the major risk factors; concepts such as Mortality or Head and Neck were positioned as emerging within the scientific literature. Conclusions: The main risk factors, i.e., alcohol and tobacco consumption, are relevant in terms of mortality in the consumer population, which is why their role should be determined in future studies.